0361 Birthplace Moderates Racial/Ethnic Disparities in Multiple Sleep Characteristics Among Non-Hispanic Whites and Hispanic/Latino Heritage Groups in the United States. (27th May 2020) - Gaston, S A; Martinez-Miller, E E; Nguyen-Rodriguez, S; Aiello, A; McGrath, J; Jackson, W; Nápoles, A; Pérez-Stable, E J; Jackson, C L
Abstract: Introduction: Sleep duration disparities by Hispanic/Latino heritage exist; however, few studies have additionally investigated sleep quality disparities by heritage and birthplace, nor have studies compared foreign-born to US-born Non-Hispanic Whites (NHWs). Methods: Using pooled 2004-2017 National Health Interview Survey data, we investigated whether sleep disparities varied by birthplace among adult NHWs and Hispanic/Latino heritage groups. Adjusting for sociodemographic and behavioral/clinical characteristics, survey-weighted Poisson regressions with robust variance estimated prevalence ratios (PRs) and 95% confidence intervals (CIs) of self-reported sleep characteristics. Sleep characteristics were compared among foreign-born NHWs and Hispanic/Latino heritage groups vs. US-born NHWs. Sleep characteristics were also compared across Hispanic/Latino heritage groups vs. foreign-born NHWs. Results: Among 254, 699 participants (Meanage ±SE: 47±0.9 years; 49% female), 81% self-identified as NHW (n=207, 154), 12% Mexican (n=30, 100), 2% Puerto Rican n=5, 077), 1% Cuban(n=2, 518), 1% Dominican (n=1, 658), and 3% Central/South American (n=8, 162). Compared to US-born NHWs, foreign-born NHWs were more likely to report >9-hours sleep duration (PR=1.11[95% CI: 1.01-1.21]) and poor sleep quality (e.g., PRtrouble staying asleep =1.27[1.17-1.37]), and US-born Mexicans were no more likely to report shorter sleep duration while foreign-born Mexicans were less likely (PR<6-hours =0.52[0.47-0.57], PR6-<7-hours =0.72[0.68-0.76]). Although US-born and foreign-born Mexicans had lower prevalence of poor sleep quality compared to US-born NHWs, PRs were lowest for foreign-born Mexicans. Compared to foreign-born NHWs, US-born Mexicans were more likely to report shorter sleep duration, but foreign-born Mexicans were no more likely. Regardless of birthplace, Puerto Ricans were more likely (e.g., PR<6-hours =1.37[1.24-1.60]) and Cubans were less likely (e.g., PR<6-hours =0.81[0.68-0.96]) to report shorter sleep duration vs. US-born NHWs. Compared to US-born NHWs, Dominicans reported better sleep duration and quality. Sleep duration and quality did not differ among Dominicans vs. foreign-born NHWs. Conclusion: Sleep disparities varied by birthplace and Hispanic/Latino heritage. Birthplace of both NHWs and racial/ethnic minority groups should be considered in disparities research. Support: This work was funded by the Intramural Program at the National Institutes of Health (NIH), National Institute of Environmental Health Sciences (NIEHS, Z1AES103325-01) and the Division of Intramural Research, National Institute on Minority Health and Health Disparities.